Labour law in times of Turbo-Capitalism - Arias Domínguez, Ángel (2019)
Since its inception, labour law surged as a response to the needs of workers who were submitted to a capitalist economy. However, with a shift to turbocapitalism, efficiency and consumption take precedent in redefi ning labor dynamics. As a result, labour law is bend to adapt to this new context. The author highlights the need of a historical revision to the content of labour law. This involves revisiting the economic context that positioned its inception to identify which elements are essential and defi ne their purpose. Finally, they detail the changes introduced through turbocapitalism as the dynamic of labour relations. From here, the author suggests a revision of the essential elements of labour law as the key to understanding this new economic era.